Reproductive particularities of water buffalo cows (Bubalus bubalis bubalis) - Hector Nava-Trujillo; Robert Valeris-Chacin; Armando Quintero-Moreno (SPERMOVA, 2019)
In this article we review the reproductive characteristics of water buffaloes. One of the most outstanding features is the lower intensity of the signs of estrus and the high proportion of silent estrus, which are related to the smaller size of the follicles and the lower production of estradiol. Another aspect of great interest is the reproductive seasonality, leading to the concentration of calving and estrus during the months of shorter photoperiod, which imposes, alongside a longer gestation, a challenge to the buffalo cow in order to achieve a calving interval of 400 days. The reproductive seasonality causes irregular milk production during the year; therefore, the occurrence of estrus during the time of long photoperiod needs to be induced in some cases. However, since both oocyte and embryo quality and luteal function are compromised during this period, the fertility is lower, which leads to a high proportion of embryonic death during this time of the year. These physiologic characteristics, the sustained increase in the water buffalo population worldwide, and the genetic improvement for milk production achieved in recent years, make it necessary for farmers and professionals to increase their understanding of the reproductive physiology of the species not only in order to maximize reproductive efficiency, but also to achieve a higher effectiveness in the application of reproductive biotechnologies.